2003
DOI: 10.1161/01.cir.0000068344.54010.b3
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Contribution of I Ks to Canine Ventricular Repolarization

Abstract: Background-In large mammals and humans, the contribution of I Ks to ventricular repolarization is still incompletely understood. Methods and Results-In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(66 citation statements)
references
References 32 publications
8
58
0
Order By: Relevance
“…β-AR signalling also influences AP duration (APD) and the relationship between APD and the diastolic interval (restitution). However, the regulation of APD by β-AR signalling is complex; the slowly activating delayed rectifier K + channel (I Ks ) is a substrate for phosphorylation by PKA; in large mammals, but not rats and mice, β-AR stimulation increases I Ks which promotes APD shortening [51,52]. In whole hearts, sympathetic nerve stimulation or addition of β-agonists increases the steepness of the slope of the APD restitution curve and reduces the effective refractory period [24,53].…”
Section: β-Adrenergic Signalling In the Heartmentioning
confidence: 99%
“…β-AR signalling also influences AP duration (APD) and the relationship between APD and the diastolic interval (restitution). However, the regulation of APD by β-AR signalling is complex; the slowly activating delayed rectifier K + channel (I Ks ) is a substrate for phosphorylation by PKA; in large mammals, but not rats and mice, β-AR stimulation increases I Ks which promotes APD shortening [51,52]. In whole hearts, sympathetic nerve stimulation or addition of β-agonists increases the steepness of the slope of the APD restitution curve and reduces the effective refractory period [24,53].…”
Section: β-Adrenergic Signalling In the Heartmentioning
confidence: 99%
“…Extensive studies have shown that K + channels essential for the cardiac AP repolarization are intricately regulated by β-adrenergic stimulation, and different K + channel I Ks , I Kr , I K1 shows different sensitivity to β-adrenergic stimulation. [28] [26] [25] [10] In all previous studies, however, I Ks , I Kr , I K1 was each recorded from different cells and using different V-clamp conditions (i.e. voltage protocol, ionic composition, Ca 2+ buffering).…”
Section: Introductionmentioning
confidence: 99%
“…1-4 Kv7.1 α subunits tetramerize to form the pore of the slowly activating delayed rectifier K + current (I Ks ) channel complex, and in the human heart, I Ks is upregulated by protein kinase A (PKA) activation to prevent ventricular action potential (AP) prolongation during β-adrenergic stimulation. 5,6 Consequently, many patients with LQT1 tend to experience life-threatening symptoms while exercising or swimming. 7,8 Unfortunately, rendering a diagnosis of LQT1 on the basis of a 12-lead ECG alone presents a significant challenge as an estimated 25% of genotype-positive individuals with LQT1 fail to display an abnormal QTc interval at rest, commonly referred to as a concealed LQT1 phenotype.…”
Section: Introductionmentioning
confidence: 99%